Components of success implementation of protective actions at attack of opponent armed by plain weapon - Bondarenko V.V (Kharkov National Pedagogical University, 2010)
The analysis of activity of worker of militia is conducted in the conditions of the real collisions with offenders. Certain and described components of opposition the attack of the armed criminal. Components of success of implementation of protective actions are in interdependence. Success of defence will depend on the presence of knowledges of conformities to law in the actions of criminal. Success of protective actions will depend on the successive mastering of knowledges, forming of abilities and skills of the timely reacting on the conduct of criminal.